DIALEKTIKA SYARIAT ISLAM DAN NEGARA - Sirajuddin M (Universitas Islam Negeri Fatmawati Sukarno, 2017)
This study aims to understand the teachings (shari’a) of Islam and explore its positionin the national life level. The method of this study is a historical-philosophical study that aims to unravel the root of the dynamic histories of Islam in Indonesia and the ideology of Pancasila in order to seek the intersection of both in an effort to strengthen the understanding and practice of Pancasila. The result of this study is that Islam as religious values can be a source of national (law) development based on the ideology of Pancasila. With Islamic values, then the national development can run better and more maximally because of the relationship between Islamic religious values and national development, so it can realize the welfare of the birth and mind